The place of lymph dissection in the treatment of cancer and the choice of surgical tactics (review article) - Nikitenko, R.; Vorotyntseva, K. (Journal of Education, Health and Sport, 2021)
Over the past years, due to increase of detection of patients with early-stage stomach cancer and colorectal cancer, and improvement of survival rate, the efforts have been made to gradually develop the concept of sentinel lymph nodes detection in order to improve postoperative quality of life. The article presents the review of the literature on the feasibility of sentinel lymph nodes intraoperative diagnosis the choice of surgical treatment of patients with tumors of the stomach and colon. Analytical work demonstrates that the real time intraoperative visualization of lymph sineses using fluorescent imaging of indocyanine green during laparoscopic surgery for stomach or colorectal cancer is possible and it is a useful method of the lymph nodes mapping, therefore it can lead to intraoperative changes at lymphadenectomy as well as to reduce the surgical injury. It indicates the need in further research and improvement of approach.